The Level of Climate Change Science Literacy among Teachers in Seychelles: Implications for the Blue Economy - Anyanwu, Raymond Ndubisi (Asian Journal of Interdisciplinary Research, 2019)
Climate change poses a serious threat to the ocean on which the Seychelles economy depends for resources and services. To address this concern, the Seychelles National Climate Change Response Strategy recommends education about climate change in all levels of the education system to nurture young people with the capacity to address climate change impacts. This quantitative, descriptive, cross-sectional survey measures the level of climate change science literacy among teachers in Seychelles on a five-point summated scale (Extremely Low, Low, Medium, High, and Extremely High). Data was collected with a 15-item Climate Change Science Literacy Questionnaire (CCSLQ) from 572 participants representing 42.62% of the population of teachers in public schools at the time of the survey. Ethical considerations relating to access, informed consent, anonymity, and confidentiality were fulfilled. Collected data was analysed statistically with descriptive techniques (percentage, means, standard error of measurement and confidence interval) and inferential technique with the Fisher’s Exact Chi-Square test. Statistical operation was performed with the Statistical Package for the Social Science (SPSS). Results indicate that the majority of the participants (37.4%, n=214) have medium literacy regarding climate change science with misconceptions on all three domains of climate change science: causes, impacts, and solutions. Educational interventions to enhance teachers’ knowledge and understanding of climate change are recommended; otherwise the teachers will transfer inaccurate concepts to the learners. Without young Seychellois with the capacity to take action on climate change, it may be wearisome for Seychelles to achieve a smooth transition to a blue economy.